Natriuretic Peptide-Induced Catecholamine Release from Cardiac Sympathetic Neurons: Inhibition by Histamine H(3) and H(4) Receptor Activation - Chan, Noel Yan-Ki (The American Society for Pharmacology and Experimental Therapeutics, 2012)
We reported previously that natriuretic peptides, including brain natriuretic peptide (BNP), promote norepinephrine release from cardiac sympathetic nerves and dopamine release from differentiated pheochromocytoma PC12 cells. These proexocytotic effects are mediated by an increase in intracellular calcium secondary to cAMP/protein kinase A (PKA) activation caused by a protein kinase G (PKG)-mediated inhibition of phosphodiesterase type 3 (PDE3). The purpose of the present study was to search for novel means to prevent the proadrenergic effects of natriuretic peptides. For this, we focused our attention on neuronal inhibitory Gα(i/o)-coupled histamine H(3) and H(4) receptors. Our findings show that activation of neuronal H(3) and H(4) receptors inhibits the release of catecholamines elicited by BNP in cardiac synaptosomes and differentiated PC12 cells. This effect results from a decrease in intracellular Ca(2+) due to reduced intracellular cAMP/PKA activity, caused by H(3) and H(4) receptor-mediated PKG inhibition and consequent PDE3-induced increase in cAMP metabolism. Indeed, selective H(3) and H(4) receptor agonists each synergized with a PKG inhibitor and a PDE3 activator in attenuating BNP-induced norepinephrine release from cardiac sympathetic nerve endings. This indicates that PKG inhibition and PDE3 stimulation are pivotal for the H(3) and H(4) receptor-mediated attenuation of BNP-induced catecholamine release. Cardiac sympathetic overstimulation is characteristic of advanced heart failure, which was recently found not to be improved by the administration of recombinant BNP (nesiritide), despite the predicated beneficial effects of natriuretic peptides. Because excessive catecholamine release is likely to offset the desirable effects of natriuretic peptides, our findings suggest novel means to alleviate their adverse effects and improve their therapeutic potential.